The Relationship between Maximum Repetitions and Body Weight That Affects the Development of Muscular Strength in Female Beginners in Strength Exercises - Saleh, Hamid (Journal of Physical Education, 2008)
Although there are many wrong concepts concerning women’s practicing strength exercises modern scientific concepts proved just the opposite . Using correct methods in training depending on their muscular abilities will have a positive effect on development performance . Men’s training load is similar to women’s training load but it is difficult to determine women’s maximum repetition . The problem of the research lies in finding the perfect method to determine light weights to develop beginners’ muscular strength . The Aims Of the research are : • Finding a relationship between maximum repetitions and body weight in female beginners in strength exercises using lifting weigths identical to the weight of the body . • Identifying the effect of maximum repetitions with body weight on the development of muscular strength in beginners. The research is conducted on (22) female students of the college of Physical Education /University of Baghdad. After finding the correlative relationships the percentage was determined 30% and 50% of the weight of the body as maximum load. According to this the subjects are divided into two experimental groups : • First Group; the training intensity was 30% of body weight as a training load . • Second Group ; the training intensity was 50% of body weight as a training load . After pre tests the two groups indulged in the proposed training program that depends on maximum repetitions for six weeks then post tests were conducted. • The researcher came up with the following results: • There is a correlative relationship between maximum repetitions and body weight in female beginners till 50% of body weight and there are nocorrelative relationships in 75% of body weight . • maximum repetitions using 30% and 50% of body weight affect muscular strength development in female beginners. Finally the researcher recommended the following : • Paying attention to programming and training muscular strengthto women because it develops their muscular strength . • Giving priority to maximum repetition method when training women